Household participation in Financial Markets - Mabale, Thato (University of the Witwatersrand, Johannesburg, 2024)
This research investigates the relationship between financial literacy and financial participation among South African households focusing on demographic variables such as age, gender, and education level. The study examines the relationship between financial literacy and financial asset investment using data from the 2019 FinScope Survey. The demographic characteristics of participants, including age, gender, ethnic group, marital status, educational level, household size, and employment status, were examined through statistical analyses (correlation and regression) to determine their influence on financial investment. The findings revealed that higher financial literacy, measured through understanding and behaviour regarding financial assets, significantly correlates with increased investment levels (β = 0.004, p = 0.012). Participants with higher numeracy skills also demonstrated greater financial participation (β = 0.005, p = 0.022). Demographic factors were similarly influential, with older individuals (β = 0.001, p = 0.035) and male participants (β = 0.001, p = 0.049) investing a higher mean percentage of their income in financial assets. Moreover, young adults aged 30–44 were found to be the most active investors, while individuals with tertiary education showed the highest mean investment percentage, showing the important role of education in improving financial engagement (β = 0.007, p < 0.001). This corroborates previous studies which found that participant characteristics affect their financial behaviour and risk tolerance. The study also highlights the influence of household size and composition, with larger households and those with more children investing significantly less due to financial constraints. Overall, these results underscore that a good understanding of financial concepts such as interest rates and inflation, leads to greater financial engagement and investment growth. An important implication of this study is that targeted interventions to enhance financial literacy mostly among women and less-educated groups, could increase financial market participation. Such efforts would promote diversity in South Africa’s financial markets and support economic development for all population groups.
A research report submitted in fulfillment of the requirements for the Master of Management in Energy Leadership, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Financial Markets; SDG-8: Decent work and economic growth